An approach to support model based definition by PMI annotations. Issue 4 (7th June 2017) - Cicconi, Paolo; Raffaeli, Roberto; Germani, Michele
ABSTRACT: PMI annotations are widely used to support the Model Based Design within modern companies. In particular, the introduction of digital annotations marks the transition from the 2D drawings to the 3D representation in many manufacturing and design companies. However, today the implementation of the PMI technology presents some limits, such as the lack of functions to generate structure templates to be applied to similar CAD models. The proposed approach aims to overcome the limits of traditional tools which are not able to add a PMI annotation's structure from one model to another one. The paper describes a method to reuse digital PMI annotations in a new model during the design phase, where the annotations are inherited from similar CAD documents. The proposed approach is based on two levels of geometric analysis: the searching of similar template models from an XML database, and the identification of the related geometric entities, which are used as associated objects for the definition of 3D annotations. The test case is focused on the automatic generation of PMI annotations for exhaust duct items used in oil & gas applications. The proposed tool has been developed within a software program called Duct Designer, which is used for the CAD automation of duct items. Particularly, the test case enhances the retrieval and reuse of sizing schemes from previous 3D models in order to obtain an automatic rebuilding of the geometric annotations. GRAPHICAL ABSTRACT: